Linking servicescape, tourist satisfaction and overall tour guiding experience: the case of Taman Negara National Park, Malaysia - Tan, Sing Ee; Abdul Aziz, Yuhanis; Awang, Khairil Wahidin; Samdin, Zaiton (Universiti Putra Malaysia Press, 2015)
This study has two key objectives. The first objective is to determine the characteristics of servicescape, while the second is to investigate the impact of servicescape on tourist satisfaction and the overall tour guiding experience. The linkages are attempted on a sample of 385 local and foreign visitors to Taman Negara National Park (TNNP) through the application of exploratory factor analysis and multiple regression. The experimental results show that: (a) there are five characteristics of servicescape in the TNNP, and (b) servicescape has a positive impact on tourist satisfaction and the overall tour guiding experience. The theoretical and managerial consequences of the findings of the study are esented and recommendations have been made for researches in the future.